(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This scientific article explores the cognitive and linguistic and cultural significance of the use of English and Latin medical terms in modern medicine. The influence of globalization on the spread of medical terminology is considered, as well as the specifics of the use of terms in various cultural contexts. The advantages and disadvantages of using English and Latin terms, as well as the trends of their use in modern medicine, are analyzed.